Perancangan Alat Pemotong Tahu di UMKM Tahu Sari Bumi Karawang dengan Pendekatan Value Engineering - Antari, Fitri Diana; Azizah, Fahriza Nurul; Adien, Aisyah Nurfadillah; Hafizhuddin, Abdullah Azzam (Fakultas Teknik Universitas Tulang Bawang, 2025)
UMKM Tahu Sari Bumi Karawang is a tofu producer that produces 20,000 tofu beans per day. As a large producer, this MSME still applies manual cutting methods, which has an impact on limited productivity and product quality. The non-uniformity of tofu size not only affects the appearance of the product but also potentially reduces customer satisfaction. In addition, the limited use of tools makes the production process slower and reduces labor efficiency. Therefore, this study aims to design a tofu cutting tool to improve time efficiency and ensure more uniform cut results. The design of tofu cutting tools uses a value engineering approach, which is a structured and function-oriented team approach to analyze various functions in a product, system, or supply process. The goal is to increase value by identifying and eliminating unnecessary costs, while ensuring the achievement of desired performance with efficient cycle costs. Based on the research results, this tool consists of five main components with food grade stainless steel material. With an investment of Rp 1,466,000, this tool has a payback period of four weeks and can save cutting time up to 77%, and produce more uniform and precise tofu pieces. Keywords: Efficiency, Product Quality, Tofu Cutting Tool, Value Engineering